Current issues - Salcedo, Lucila L.; Peralta, Ana Maria R.;Ronquillo, Adelaida A.;Fontanilla, Ofelia L ;Espiritu, Socorro C (Quezon City, Philippines : Katha Publishing Co, Inc., 2002)
The new edition of the book has been further enriched and improved through the addition of new chapters which the authors felt are current and presently discussed by most gatherings of people who are news and people oriented.
Chapter 1- Population and related issues -- Chapter 2- Marriage and the family: nature and scope -- Chapter 3- Family disorganization: nature and scope -- Chapter 4- Family planning: for a better quality of life for the Filipino -- Chapter 5- Social values and social conscience -- Chapter 6- The concept of human rights -- Chapter 7- The Nature of graft and corruption -- Chapter 8- The Philippine health problem -- Chapter 9- Poverty in the Philippines -- Chapter 10- Common forms of malnutrition afflicting filipinos -- Chapter 11- The Concept and nature of ecology -- Chapter 12- Drug abuse: education, prevention and control -- Chapter 13- Terrorism and the Abu Sayyaf group
Includes bibliographical references and index.
Keywords: SOCIAL PROBLEMS